Investigation of High-Intensity Ion Beam Generation in the Diode with External Magnetic Insulation and Explosive Plasma Emission Source; Russian Physics Journal; Vol. 60, iss. 12 - Shamanin V. I. Vitaly Igorevich (2018, 2018)
Title screen